An assessment of health profile and body pain among construction workers. Issue 3 (19th September 2020) - Umar, Tariq; Egbu, Charles; Honnurvali, Mohamed Shaik; Saidani, Messaoud; Al-Mutairi, Matira
Abstract : Construction is one of the most hazardous and complex industries worldwide, which may result in the most fatal accidents and occupational illnesses. It is also regarded as a major industry not only in Gulf Cooperation Council (GCC) countries but also worldwide and it is rapidly growing. This study reports an assessment of different body parameters, including physiological factors and body pain of construction workers from GCC countries. Demographic data were collected by way of face-to-face interview followed by the measurement of body mass index, blood pressure and heartbeat. Data for musculoskeletal pain were collected through a structured questionnaire. The results reveal that a majority of workers were overweight or obese. The blood pressure of 43·3% of the participants was more than the threshold and shows hypertensive values. An estimate of 46·6% of the workers experienced body pain in the last three months, while the most frequently reported areas for pain were neck, shoulders, low back, legs and knees. Sleep patterns were one of the causative factors that led to experience of pain among workers. This research study would be helpful to develop strategies to improve the well-being of construction workers in GCC countries.